Lunjika SDA Mission in Northern Malawi 1932 - 1995 - Banda, Macleard (Mzuni books ;, 2018)
The missionary work of the Seventh-day Adventist Church started in Southern Malawi in 1902, and histories of churches are usually told from that starting point. This book uses a different approach, it tells the story of Lunjika Mission (earlier called Mombera Mission) which begins in 1932, showing how the SDA Church met a new culture, that of the strongly patrilineal Ngoni and their neighbours to the North, and how it dealt with other churches that had started missionary work in that broad area up to two generations before.